THE INFLUENCE OF DIGITAL MARKETING ON IMPROVING MARKETING PERFORMANCE IN CAFES IN KALIBARU DISTRICT, BANYUWANGI REGENCY - Sunarto, Danar Aldova; Santoso, Budi; Wibowo, Yohanes Gunawan (Dynamic Management Journal, 2024)
This research aims to determine and analyze the influence of digital on marketing performance at cafes in Kalibaru District, Banyuwangi Regency. The location of this research is at 3 cafes in Kalibaru District, namely Cafe Anyo, Roemah Kopi Kalibaroe and Pawon Rencang Lawas. This type of research uses quantitative methods with a sample size of 120 respondents and uses purposive proportional random sampling techniques using data collection techniques in the form of questionnaires to respondents. The data analysis technique for this research uses instrument testing, classical assumptions and multiple linear regression. The analysis results obtained show that social media Instagram, E-commerce and social media Tiktok have a positive and significant effect, both partially and simultaneously, on marketing performance at cafes in Kalibaru District, Banyuwangi Regency, with a contribution level of influence of 0.540 or 54%.